Case Report: A rare pediatric case of B-cell lymphoblastic lymphoma presenting as an isolated renal mass with EWSR1::FLI1 translocation and germline CHEK2 variant - Daniels, Katelyn P.; Nichols, Kim E.; Pandey, Arti S.; Gheorghe, Gabriela; Helmig, Sara; Garrett, Kevin; Bag, Asim K.; Inaba, Hiroto; Ribeiro, Raul (Frontiers in Pediatrics, 2025)
We describe a 5-year-old boy who initially presented with a large left renal mass, suspected to be Wilms tumor (WT). However, biopsy results revealed B-cell lymphoblastic lymphoma (B-LBL) manifesting as an isolated renal mass. Tumor transcriptome analysis identified an EWSR1::FLI1 fusion, with breakpoints distinct from those typically associated with Ewing's sarcoma. Other somatic pathogenic variants affecting WT1, ETV6, SETD2, ADD2, EZH2, PRDM2, and NF2 were identified. The patient also carried a germline CHEK2 variant of unknown significance, raising concerns for cancer predisposition. Given the unusual clinical presentation, somatic and germline genetic findings, and impossibility of measuring early response to therapy, the classical treatment of lymphoblastic lymphoma was modified. To minimize exposure to agents that increase DNA breakage, blinatumomab was used for consolidation. This approach led to significant tumor regression and the patient remains in remission for eight months post-diagnosis. This case underscores the importance of precise diagnosis, comprehensive somatic and germline genetic evaluation, and adapted treatment in pediatric oncology.